Decomposition kinetics and postmortem production of hydrogen sulfide and its metabolites. (November 2022) - Wang, Ruili; Fan, Zheyu; Wei, Zhiwen; Wang, Lele; Wang, Tao; Li, Wenyue; Ma, Dong; Guo, Zhongyuan; Yun, Keming
Abstract: Background: Hydrogen sulfide (H2 S), an endogenous gas, can also be generated from organics putrefaction. It is difficult for suspected cases of H2 S poisoning to determine whether H2 S in specimens is ingested by antemortem poisoning or generated from organics putrefaction. The aim of this study was to find the biomarkers of acute H2 S poisoning via comparing the concentrations of H2 S and its metabolites over time in specimens. Methods: The H2 S-spiked blood and blank blood group were established. The decomposition kinetics and the postmortem production of H2 S were studied due to organics putrefaction. The specimens were placed under 4 conditions of 37, 20, 4 and − 20 ℃. The content of H2 S in specimens was quantified by gas chromatography-mass spectrometry, and the contents of its metabolites (thiosulfate and trimethylsulfonium) were measured by liquid chromatography-mass spectrometry, and the variation of its concentration was evaluated. Results: In H2 S-spiked blood, H2 S decreased sharply in the initial stage at 37, 20 and 4 °C, and increased first and then decreased later; but it was relatively stable at − 20 °C. In spiked blood, thiosulfate was 9-fold higher than endogenous concentrations, which increased at first and then decreased during storage. Except for thiosulfate at 37 °C, H2 S and thiosulfate in blank blood both increased at first and then decreased in storage; but trimethylsulfonium (TMS) gradually decreased over time in both groups. Conclusions: Thiosulfate is a reliable biomarker of acute H2 S poisoning at − 20℃ within 7 days. But H2 S, because of instability and volatility, is not an ideal poisoning marker. TMS is not an appropriate biomarker due to extremely low concentration in blood. Highlights: Hydrogen sulfide, thiosulfate and trimethylsulfonium were evaluated in the bloods. The biomarkers of hydrogen sulfide poisoning were sought. Decomposition kinetics of hydrogen sulfide were studied. Putrefactive production of hydrogen sulfide and its metabolites was studied.